Analysis of basic technical abilities of sepaktakraw athletes - Hanafi, Muhamad; Padli, Padli; Yendrizal, Yendrizal; Donie, Donie (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2024)
Problems: The problem in this research is that the level of basic technical ability of PSTI sepak takraw athletes in Padang Panjang City is still unknown. . Purpose: The aim of this research was to determine the level of basic technical ability of PSTI sepaktakraw athletes in Padang Panjang City. Methods: This type of research is descriptive. This research was carried out on February 1 2024 at the PSTI Sepaktakraw Field, Padang Panjang City. The population in this study was 15 PSTI Padang Panjang City sepak takraw athletes. The sampling technique used was Purposive Sampling . The instrument in this study was a test of technical abilities relating to: controlling and holding the ball for 3 minutes for sila soccer, turtle kicks, kicks or head games. Data was analyzed using percentages. The Results: results of the research based on data analysis are that the average athlete's kicking ability is 204 in the very good category, the average athlete's kicking ability is 244 in the fair category, the average athlete's walking ability is 179 in the very good category, the average athlete's heading ability is 125 with the less category. Conclusion: After averaging the basic sepaktakraw technique, the result was 188.4, which fell into the